Local action of the proinflammatory cytokines IL-1β and IL-6 on intracranial meningeal nociceptors - Zhang, Xichun (2011)
BACKGROUND: Peripheral nociceptive action of the proinflammatory cytokines IL-1β and IL-6 has been implicated in the pathogenesis of numerous pain syndromes. An increase in the level of these cytokines in jugular venous blood has been reported during migraine attacks, suggesting their potential involvement in mediating the intracranial headache of migraine. METHODS: In this work we examined, using in vivo single-unit recording of meningeal nociceptors in the trigeminal ganglion of anesthetized rats, whether the peripheral actions of IL-1β and IL-6 can promote the activation and sensitization of nociceptors that innervate the intracranial meninges, two neural processes that are believed to play a key role in promoting the intracranial throbbing pain of migraine. RESULTS: We found that meningeal application of IL-1β leads to the activation and mechanical sensitization of about 70% and 45% of the nociceptors respectively. In contrast, IL-6 was a very poor modulator of meningeal nociceptors' response properties affecting overall only about 20% of the nociceptors. CONCLUSIONS: Our study provides for the first time in vivo electrophysiological evidence that meningeal action of IL-1β can promote the activation and increased mechanosensitivity of intracranial meningeal nociceptors and that IL-6 generally lacks these properties. Future studies are required to examine the mechanism that plays a role in mediating the nociceptive effects of IL-1β on meningeal nociceptors, which may serve as a target for migraine therapy.